(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Hemp products are recognised as food by FSSAI. The hemp industry’s economic opportunities have been expanded by the recent FSSAI notification to sell and utilise hemp products as food components. Let’s talk about what hemp is and how the new FSSAI guidelines will affect it. How is cooking with hemp done? Hemp seed oil that has been cold-pressed has a subtle, nutty flavour that is excellent in salad dressings and for spreading over roasted vegetables. It can also be used for cooking, although because it has such a low smoke point, rapid sautés and stir-fries are more suited to it than deep frying. National law permits the use of medical cannabis with a license, and CBD oil produced in accordance with the Drugs and Cosmetics Act may be obtained and used legally. According to Drugs and Cosmetics